Flotation and entrainment behavior of minerals in talc-calcite separation - Akdemir, Ü; Güler, T; Yildiztekin, G (Blackwell Publishing, 2005)
The main aim of a flotation process is to recover the valuable part of the ore with minimum gangue contamination by different mechanisms, such as entrainment. In this study, the flotation rate and recovery of talc and entrainment of fine calcite particles were investigated using individual minerals and a mixture of talc and calcite. The effects of various frothers were tested. The results indicated that the type of frother had significant effects on the recovery, flotation rate and fine gangue entrainment. The addition of kerosene as a collector enhanced selectivity between talc and calcite without any reduction in talc recovery. This was attributed to increasing the rate constant of talc upon kerosene addition without any increase in the calcite fines recovery.
Keywords: calcite; entrainment; flotation rate; frother; talc